Sustainability of small dams for livestock and farming, a case study from Chitongo dam, rural Zambia - Serrao, Livia; Caridi, Simone; Farrokhi, Ali; Avesani, Diego; Kamamba, Muyaka; Galli, Mireille; Chibwe, Chalwe; Medici, Federica; Treccani, Sara; Kabika, Joel; Banda, Kawawa; Bezzi, Marco; et al. (Frontiers in Water, 2025)
Small earth dams are common water harvesting techniques in drylands, but assessing their sustainability and long-term socio-environmental impacts is hindered by limited data availability that characterize many community-scale rural contexts. This study aims to investigate the sustainability of a small earth dam in rural drylands of Sub-Saharan Africa and to discuss the possible impacts of such new infrastructure on the local socio-hydrological system. A multidimensional approach that integrates resident interviews, topographical surveys, climate time series, stream sediment transport and Digital Elevation Model analysis is proposed and illustrated with reference to a recently constructed small dam in the Chitongo community, Namwala District, Zambia. We constructed a water consumption curve under various allocation scenarios, quantifying the reservoir’s capacity to meet current demands and to support future ones for agricultural and livestock in the dry season. The households with potential access to the new water source are quantified through spatial analysis. The potential catchment sediment yield to the reservoir is estimating by integrating the RUSLE soil erosion method with a measure of sediment connectivity, suggesting the reservoir may fill up in 25 years or more, highlighting its vulnerability to siltation. The proposed approach allows assessing the multi-dimensional sustainability of small dams. Possible emerging impacts on the local socio-hydrological system are discussed from the developed baseline, also considering benefits distribution within the local community. Such a scalable approach can be adopted to support the development of regional programs for rural water security in drylands, which should engage local actors in water allocation and reservoir maintenance plans for ensuring its functioning and fair benefits distribution for a reasonable time span.